Characterization of construction and demolition wastes for civil engineering uses - João A. Paschoalin Filho (Journal of Urban Technology and Sustainability, 2020)
Construction and demolition wastes have been studied by technical means to develop management tools to reduce environmental impacts. Among the methods evaluated, recycling can be highlighted. This article demonstrates the characterization of engineering parameters for concrete construction wastes obtained at a C&DW recycling plant near São Paulo. To this end, laboratory tests were performed according to relevant technical standards to determine the following characteristics: specific weight, integrity using ultrasound, compressive strength, elasticity modulus, and absorption. The parameters obtained may serve to characterize the waste under study, as well as initial values for the development of basic civil engineering projects with low structural responsibility.